Speckle Tracking Echocardiography in Pediatric and Congenital Heart Disease. - Forsey, Jonathan; Friedberg, Mark K; Mertens, Luc (Echocardiography, 2013)
Assessment of myocardial strain using speckle tracking echocardiography is an emerging echocardiographic technique that is increasingly used in the diagnosis and management of acquired heart disease in adults. In pediatric heart disease, this is still mainly considered as a research tool as the application of this technology has been slowed by the lack of vendor-independent technology and of normative data across the different age ranges. We believe that the technology has potential applications for the early detection of myocardial dysfunction, the quantification of ventricular function in congenital heart disease, and the detection of dyssynchrony.